Age- and Sex-Specific Risks of Major Cardiovascular Complications and All-Cause Mortality Following Elective Hip and Knee Arthroplasty in the Netherlands: A Dutch Hospital Data Registry Study - Mark J.R. Smeets, MD; Maaike G.J. Gademan, PhD; Rob G.H.H. Nelissen, MD, PhD; Suzanne C. Cannegieter, MD, PhD; Banne Nemeth, MD, PhD (Arthroplasty Today)
Background: Age and sex are well-known risk factors for cardiovascular complications and mortality following total hip arthroplasty (THA) and total knee arthroplasty (TKA). Yet, stratified up-to-date absolute risk estimates, which are needed to optimize prevention, are lacking. Methods: All Dutch patients who had a first primary THA and TKA for osteoarthritis between 2015 and 2021 were included. Data on baseline characteristics, procedures, and outcomes were obtained from the Dutch Hospital Data and Population registries, after linkage. Overall risks for venous thromboembolism, arterial thromboembolism, bleeding, and all-cause mortality were estimated at 30 and 90 days following surgery. Time trends were assessed by plotting 90-day risks by year. Lastly, 90-day risks were stratified by age and sex categories. Results: A total of 123,809 THA and 132,726 TKA patients were included. Females accounted for 63% and 65% of THA and TKA patients, respectively. At 90 days, overall risks were all below 1%. We observed no clear time trends in the risks over recent years. The stratified analysis showed that especially men older than 80 have a complication risk of at least 3%. Interestingly, the risk of venous thromboembolism and bleeding, following a THA, was observed to be relatively high in men and women in the youngest age category. Conclusions: Generally, the 90-day incidence of cardiovascular complications and all-cause mortality is low but can be at least 3% for men in the highest age category. With this knowledge, perioperative preventive measures can be targeted more precisely, and shared decision-making improved.